2022
DOI: 10.3390/foods11020228
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enzymatic Hydrolysis and Microfluidization on the Techno-Functionality of Oat Bran in Suspension and Acid Milk Gel Models

Abstract: Oat bran is a nutritionally rich ingredient, but it is underutilized in semi-moist and liquid foods due to technological issues such as high viscosity and sliminess. The aim of this work was to improve the technological properties of oat bran concentrate (OBC) in high-moisture food applications by enzymatic and mechanical treatments. OBC was hydrolyzed with β-glucanase (OBC-Hyd) and the water-soluble fraction (OBC-Sol) was separated. OBC, OBC-Hyd and OBC-Sol were further microfluidized at 5% dry matter content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…After extraction, the physical properties and M w of isolated β - d -glucan undergo modifications by various treatments [ 50 ]. For example, the enzymatic treatment and micro-fluidization of oat β - d -glucan reduces both M w and the average size of particles, increases extractability up to 80%, water retention capacity, decreases the viscosity of the β - d -glucan suspension, and increases colloidal stability [ 95 ]. Roubroeks et al [ 88 ] used cellulase (EC 3.2.1.4) from Trichoderma sp to partially depolymerize oat β - d -glucan.…”
Section: Preparation Of Oat β - D ...mentioning
confidence: 99%
“…After extraction, the physical properties and M w of isolated β - d -glucan undergo modifications by various treatments [ 50 ]. For example, the enzymatic treatment and micro-fluidization of oat β - d -glucan reduces both M w and the average size of particles, increases extractability up to 80%, water retention capacity, decreases the viscosity of the β - d -glucan suspension, and increases colloidal stability [ 95 ]. Roubroeks et al [ 88 ] used cellulase (EC 3.2.1.4) from Trichoderma sp to partially depolymerize oat β - d -glucan.…”
Section: Preparation Of Oat β - D ...mentioning
confidence: 99%
“…After α-amylase–alkali treatment of oat milk, Babolanimogadam et al (2023) discovered that compared with the untreated group, oat milk yield, and protein extraction increased significantly, especially the protein extraction rate, which was approximately 80% and 60%, respectively, and the protein concentration was significantly higher than that of other treatments ( Babolanimogadam et al, 2023 ). Similarly, β-glucan, a dietary fiber rich in oats that exhibits an effect on the sensory properties of oat milk to some extent, increases the viscosity of oat milk, and β-glucan with high molecular weight (Mw) tends to form a semisolid ( Lyly et al, 2003 , Rosa-Sibakov et al, 2022 ). Therefore, it is necessary to depolymerize β-glucan by enzymes to generate a suspension of β-glucan with low viscosity and high concentration ( Sibakov et al, 2013 ).…”
Section: Prospects For Oat Milk Production and Quality Improvementmentioning
confidence: 99%
“…It was found that more phenolic compounds were detected in urine after β-glucan was ingested with a low Mw (82 kDa) compared to a high Mw (1000 kDa) and a medium Mw (524 kDa) ( Hakkola et al, 2020 ). It has been demonstrated that the Mw of β-glucan could be significantly reduced from 2748 kDa to 893 kDa and 350 kDa with the treatment of oat bran concentrates with β-glucanase, reducing the concentration of concentrate and improving the water holding capacity ( Rosa-Sibakov et al, 2022 ). Therefore, the selection and technology of enzymes affect the taste, flavor, and nutritional properties of oat milk.…”
Section: Prospects For Oat Milk Production and Quality Improvementmentioning
confidence: 99%
“…According to the American Food and Drug Administration (FDA), the positive effects of β-glucan on health can occur when 0.75 g is consumed per serving [ 21 ] and the daily intake of β-glucan recommended by the FDA is 3 g [ 19 , 22 ]. Technologically, β-glucans are also functional depending on their molecular weight (Mw), source of origin, extraction method, and degree of purification [ 23 , 24 ]. Oats are the most important known sources of natural β-glucan; with a content of 3–7% [ 19 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%